2009
DOI: 10.1038/sj.bjc.6605427
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of residual tumour by FDG-PET: conventional imaging and clinical examination following primary chemotherapy of large and locally advanced breast cancer

Abstract: BACKGROUND: The aim of this was to evaluate FDG-PET (2-(fluorine-18)-fluoro-2-deoxy-D-glucose positron emission tomography) for assessment of residual tumour after primary chemotherapy of large and locally advanced breast cancer in comparison with conventional imaging modalities. METHODS: In a prospective multicentre trial, 99 patients underwent one or more breast imaging modalities before surgery in addition to clinical examination, namely, FDG-PET (n ¼ 89), mammography (n ¼ 47), ultrasound (n ¼ 46), and magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 33 publications
0
36
1
Order By: Relevance
“…This specificity should allow facile differentiation of proximal malignant from inflamed regions of the same organ or tissue. The improved specificity could prove useful when recurrence of cancer is suspected near the site of a prior surgery and standard imaging methodologies cannot distinguish between the inflammation caused by the surgery and any residual malignant disease (32). This specificity might also be beneficial to autoimmune disease patients who have undergone prolonged treatment with immunosuppressant.…”
Section: Discussionmentioning
confidence: 99%
“…This specificity should allow facile differentiation of proximal malignant from inflamed regions of the same organ or tissue. The improved specificity could prove useful when recurrence of cancer is suspected near the site of a prior surgery and standard imaging methodologies cannot distinguish between the inflammation caused by the surgery and any residual malignant disease (32). This specificity might also be beneficial to autoimmune disease patients who have undergone prolonged treatment with immunosuppressant.…”
Section: Discussionmentioning
confidence: 99%
“…However, evaluation at the end of NAC cannot provide the opportunity to change treatment. Moreover, studies that investigated PET performance at different time points showed that PET has a lower sensitivity to predict residual disease when performed at the end of chemotherapy (11).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, comparison of PET/CT to morphologic imaging results was not performed, because patients had either CT or MR imaging at the initial work-up. 18 F-FDG PET/CT has been used to assess response to NACT in non-IBC patients (7,10,(17)(18)(19)(20)(21)(22). Published data show a higher baseline 18 F-FDG uptake in patients with pCR than in patients with a poorer response (7,17).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also evaluated the performance of 18 F-FDG PET/CT after completion of NACT to predict pCR (21,22) and found that 18 F-FDG PET did not accurately assess residual tumor. Similar results were observed in the present study, as mean SUV max on PET3 did not significantly differ between the pCR and nonpCR groups.…”
Section: Discussionmentioning
confidence: 99%